Efficacy and Safety of Ketone Supplementation or Ketogenic Diets for Alzheimer's Disease: A Mini Review - Lilamand, Matthieu; Mouton-Liger, François; Di Valentin, Emmanuelle; Sànchez Ortiz, Marta; Paquet, Claire (Frontiers in Nutrition, 2022)
Alzheimer’s disease (AD) is the most frequent age-related neurodegenerative disorder, with no curative treatment available so far. Alongside the brain deposition of β-amyloid peptide and hyperphosphorylated tau, neuroinflammation triggered by the innate immune response in the central nervous system, plays a central role in the pathogenesis of AD. Glucose usually represents the main fuel for the brain. Glucose metabolism has been related to neuroinflammation, but also with AD lesions. Hyperglycemia promotes oxidative stress and neurodegeneration. Insulinoresistance (e.g. in type 2 diabetes) or low IGF-1 levels are associated with increased β-amyloid production. However, in the absence of glucose, the brain may use another fuel: ketone bodies (KB) produced by oxidation of fatty acids. Over the last decade, ketogenic interventions i.e. ketogenic diets (KD) with very low carbohydrate intake or ketogenic supplementation (KS) based on medium-chain triglycerides (MCT) consumption, have been studied in AD animal models, as well as in AD patients. These interventional studies reported interesting clinical improvements in animals and decrease in neuroinflammation, β-amyloid and tau accumulation. In clinical studies, KS and KD were associated with better cognition, but also improved brain metabolism and AD biomarkers. This review summarizes the available evidence regarding KS/KD as therapeutic options for individuals with AD. We also discuss the current issues and potential adverse effects associated with these nutritional interventions. Finally, we propose an overview of ongoing and future registered trials in this promising field.